A Novel Study for a Class of Nonlinear Fuzzy Fractional Volterra-Fredholm Integro-Differential Equations - Sharif, Abdulrahman A.; Hamood, Maha M.; Hamoud, Ahmed A.; Ghadle, Kirtiwant P. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we aim to prove new results about the existence and uniqueness of solutions to fuzzy fractional Volterra-Fredholm integro-differential equations (FFV-FIDEs). These equations include fuzzy beginning conditions and generalized fuzzy Caputo-Hukuhara differentiability. The consecutive iteration approach and the Banach fixed point theorem are used in the proof. An example is provided to illustrate the main results.